The possible impact of cervical stenosis on cephalad neuronal dysfunction. (September 2018) - Khachatryan, Tigran; Robinson, Joe Sam
Abstract: Earlier observers have speculated on the causal relationships between abnormal CSF circulation and a variety of neurological dysfunctions. Such speculations have been at least partially validated by recent evidence and inquiries contravening the traditional static viewpoint of CSF circulation. More contemporary inquiries establish a number of factors which influence both CSF production and absorption (sleep disturbance, neck position, cerebral metabolism, brain atrophy, medications, etc.). Thus, transient periods of abnormality are possibly mingled with periods of normality. Such episodic alterations suggest that the physiological arrangements which underpin CSF circulation may be in some ways likened to blood pressure alterations, in that long-standing CSF abnormalities may be both unappreciated and gradual, though virulent enough to cause substantial neurological injury. We suggest that cervical stenosis (blocking an important CSF decompressive pathway into the vertebral canal) is among the largely unappreciated causes of abnormal CSF circulation and may play a role in cephalad neuronal dysfunction. Such a blockage is correlated with age and easily assessed by cine MRI study. Indeed, episodic disturbances can diminish CSF cerebral flow circulation increasing deposition in cerebral parenchyma of contrary metabolic products (e.g. beta Amyloid), possibly having a causal influence on senile dementia. Additionally, cervical stenosis, by increasing posterior fossa cerebral pressure, could play a causal role in a number of afflictions, among them sleep apnea, concomitant respiratory and circulatory dysfunction, hypertension, chronic occipital headaches, tinnitus, etc. We further suggest that among those patients with substantial cervical stenosis (extensive enough to block CSF circulation in the cervical area as identified by cine MRI) appropriate comparative clinical studies could be undertaken to demarcate associations with presenile dementia, sleep disturbance and posterior fossa dysfunction. Additionally, we suggest that an intracranial monitoring implant be perfected to chronically monitor both intracranial pressure and CSF flow – a monitoring device comparable to the rather less invasive sphygmometric evaluation of blood pressure. If such speculations prove correct, different therapeutic regimens which might improve outcome could be imagined. Among them better sleep hygiene (to by position maximize CSF flow) and possibly more aggressive operative decompressive intervention to diminish cervical obstruction.